Effectiveness of competitive performance of basketball team - Kudryashov, E. V. (Theory and Practice of Physical Culture, 2019)
Competitive performance is known to depend on multiple factors of the training and competitive processes - that are particularly challenging in the modern team sports due to the flows of players, frequent changes in the rules of competitions and many other things. We made an attempt in our study to address these issues by the competitive performance rating toolkit offered by a new basketball statistics processing software system. Sampled for the study were women basketball players (n=85) ranging in qualifications from Class III to Candidate Masters of Sport. Based on the study data and analyses we found the new basketball statistics processing system being beneficial for the practical competitive performance rating, training process design and management purposes. The multisided competitive performance statistics proved to improve the team performance control and management by the coaching team, better understanding of the game by each player, determination and responsibility in the teamwork. We recommend the new software for application in the training and competitive processes for timely corrections to the competitive performance.